Method and Rate of Fertilizer Application in Bajra Varieties under Barani Condition - Mehta, U R; Shekhawat, G S; Mathur, B N (Annals of Arid Zone, 2016)
A field trial was conducted at the Government Agriculture Farm, Mahdore (Jodhpur} for three kharij seasons (1963 to 1965) to study theÂ· effect of two different levels of nitrogen, applied in single or in split doses; with phosphatic fertilizer (broadcast and drilled) and without phosphatic fertilizer on the grain yield of bajra (var. chadi and R. S. J.). Both the varieties yielded at par, there was no difference in yield due to broadcast or placement of phosphatic fertilizer. Basal application of 30 Kg N!ha with 15 Kg P205 provided the highest yield.